The Impact of Negative Externality of Waste on The Coastal Beach of Lampung for The Community from an Islamic Economic Perspective - Fanny Budhi Kusuma; Habib Ali Pratama; Hermawan Aulia; Dania Hellin Amrina (Universitas Muhammadiyah Yogyakarta, 2022)
The impact of negative coastal externalities in Lampung Bay has produced waste that pollutes the marine environment around the coast of Lampung Bay. Although it is not visible to the naked eye, residents feel negative impacts that have become serious problems that have not yet been entirely handled. This article aims to research, study and produce decisions regarding the externalities felt by the surrounding community regarding the impact of negative externalities generated from waste which is the source of all environmental problems in Lampung Bay, and what consequences they have from an Islamic economic perspective. In our research, the method used is field research carried out directly in the field based on population and sampling to determine the negative impact of waste on the community. Garbage is produced from a production process that inevitably has negative and negative externalities. The testimonies of residents, several magazines, and direct observations led this article to the conclusion that it is essential to conduct a particular study to decide which negative externality impact is more dominant regarding the causes of continued accumulation of waste from year to year as well as the factors and implications of problems related to waste in Lampung Bay.